Analysis of Mathematics Learning Motivation for Class VII Students at SMP Negeri 5 Kisaran - Helmira, Tiara; Anim, Anim (Lembaga Riset Mutiara Akbar NOMOR AHU-0003295.AH.01.07 TAHUN 2021, 2024)
This research aims to determine the level and analyze the mathematical learning motivation of class VII students at SMP Negeri 5 Kisaran. This research is descriptive qualitative research. The subjects of this research were class VII students at SMP Negeri 5 Kisaran. The sample in this research was 25 students of class VII of SMP Negeri 5 Kisaran. From the research that has been carried out, it can be concluded that class VII students of SMP Negeri 5 Kisaran have three levels of motivation, namely 13 people (52%) with a high level of learning motivation, 10 people with a moderate level of motivation (40%), and 2 people with a low level of motivation ( 8%). Meanwhile, in the analysis of the aspects of the questionnaire given, the average percentage of students' mathematical learning motivation was 8 indicators of learning motivation and 15 statements. The average percentage of students' learning motivation was 73.25% with high criteria. This is shown from the 8 indicators provided and student statements, 6 of which are at high criteria, so it can be concluded that students' high curiosity and motivation in learning is proven by the students' efforts to dig up information themselves regarding the subject matter to be studied.